Pengaruh Budaya Organisasi dan Kompetensi Terhadap Kinerja Karyawan - Chairani, Zahara Ayu (Jurnal Ilmu Manajemen, 2024)
This research attempts to identify the effect of organizational culture and competency on employee performance. The independent variables of this research are organizational culture and competency. Meanwhile, the dependent variable is employee performance. The population of this research is the employees from PT XYZ. The sample was selected using saturation sampling, 48 respondents were obtained. Using Partial Least Square (PLS) analysis with SmartPLS 4,0, this research finds organizational culture doesn’t affect employee performance of PT XYZ. This means that the greater the organizational culture of PT XYZ, it doesn’t increase their employee performance. On the other hand, competency has a positive and significant effect on employee performance. This means that a greater employee’s competency will increase employee performance. For all employees at PT XYZ, they must continue to improve the quality of their work well in all matters within the Company. For PT XYZ, they can increase the quantity and quality of their employees by holding training or workshops.